1992
DOI: 10.1017/s002185960006809x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal undernutrition during mid-pregnancy in sheep: variable effects on placental growth

Abstract: SUMMARYThe effect of maternal undernutrition between the 30th and 96th day of pregnancy on placental growth in single-bearing ewes was determined separately in two experiments in consecutive years (1986 and 1987) at Mount Derrimut Field Station, Deer Park, Australia. In the first experiment, placental growth measured on the 96th day of pregnancy was reduced (473 v. 596 g) by maternal undernutrition, while in the second, placental growth was increased (600 v. 496 g). Foetal weight and its linear dimensions on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 17 publications
6
46
1
Order By: Relevance
“…Whilst previous studies (Mellor, 1983;Holst et al, 1992;McCrabb et al, 1992) have shown an effect of level of nutrition during mid-pregnancy on subsequent lamb birth weight, the current study illustrates that the impact of plane of nutrition, as impacted by herbage allowance, is influenced by frequency of herbage allocation. At the high herbage allowance offering herbage twice weekly reduced lamb birth weight probably due to a higher forage and subsequently ME intake.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Whilst previous studies (Mellor, 1983;Holst et al, 1992;McCrabb et al, 1992) have shown an effect of level of nutrition during mid-pregnancy on subsequent lamb birth weight, the current study illustrates that the impact of plane of nutrition, as impacted by herbage allowance, is influenced by frequency of herbage allocation. At the high herbage allowance offering herbage twice weekly reduced lamb birth weight probably due to a higher forage and subsequently ME intake.…”
Section: Discussioncontrasting
confidence: 40%
“…The ewes in the current study were shorn in mid-September; consequently, heat stress is unlikely to effect lamb birth weight. Previous studies (McCrabb et al, 1992) have shown that feeding ewes that were in good condition at the beginning of the study (day 30), above maintenance requirement, reduced placental size, which is positively correlated with lamb birth weight. However, Muñ oz et al (2008) showed that increasing feed level in mid-pregnancy from 0.8 to 1.4 maintenance did not influence birth weight.…”
Section: Discussionmentioning
confidence: 83%
“…Clearly, detailed examination of maternal body composition following nutrient restriction in early to mid gestation is required to determine if this is accompanied by appreciable loss of maternal fat stores. The observation in the present study that nutrient restriction was associated with a smaller rather than a larger placenta as observed when ewes are under-fed and lose weight (McCrabb et al 1991), suggests that major factors determining placental, and possibly fetal responses to nutrient restriction are both maternal body weight (McCrabb et al 1992;Robinson et al 1994) and body conformation (Clarke et al 1997).…”
Section: Maternal and Fetal Responses To Nutrient Restrictionsupporting
confidence: 49%
“…The most important factor is probably the placental capacity to deliver sufficient nutrients in late gestation (Bell, 1995). Placental development in turn is influenced by maternal age, parity, size and nutritional status (McCrabb et al, 1992;Osgerby et al, 2003, Wallace et al, 2005. The maternal uterine environment has a greater influence on weight at birth than the paternal genotype, although the sire does influence gestation length and birth height (Swali and Wathes, 2006).…”
Section: Prenatal Programmingmentioning
confidence: 99%